Reconciliation as possible present: girls and boys in the armed conflict - López-Cano, Carlos Enrique (2023)
This article presents the results of a research aimed at understanding the meaningsand political practices of children in vulnerable situations in Eje Cafetero, Antioquiaand Bogotá (Colombia), in relation to peace, reconciliation and democracy. Thestudy was based on political ontological hermeneutics, which provided elements tomake a reading and ¿provide an understanding of transformations from narratives,reconciliation and peace building. The results reveal that the construction of children aspolitical subjects of reconciliation is given from a creative reading of reality differentfrom that of adults, given that children live reconciliation on a daily basis through playand games.